Political Communication Strategy of The Candidate Pair Al Haris and Abdullah Sani in Winning The 2020 Jambi Gubernatorial Election - Saputra, Dedi (Devotion : Journal of Research and Community Service, 2023)
The purpose of this study was to determine the political communication strategy and the inhibiting factors and opportunities for political communication of the Al Haris and Abdullah Sani winning team. In an effort to obtain victory in the contestation of the Governor's Election in Jambi Province in 2020, which is pursued through careful political communication planning, the dissemination of issues regarding the candidate pair competing for the number one seat in the government is important to achieve victory. This research uses a qualitative descriptive method. Researchers use Political Marketing theory with three approaches, namely: push marketing, pull marketing, pass marketing. In this study the author took four informants as samples. Data collection in this study was collected from observations, interviews, and documentation. From the results of the study, there were several roles performed by the Al Haris and Abdullah Sani winning team during the campaign period, the campaign strategy was carried out in three ways: face-to-face campaigns, campaigns using social media, and open campaigns. The obstacles experienced by the winning team of Al Haris and Abdullah Sani in the field are semantic factors, namely the lack of solid coordination and communication between the winning team and perceptual distortion, namely errors caused by the narrow thinking of novice voters so that it is quite difficult to convey the programs and vision and mission of the candidate pair.